An Examination of Changes in Specialists’ Posted Price Schedules - Kavajecz, Kenneth A.; Odders-White, Elizabeth R. (Review of Financial Studies, 2001)
New York Stock Exchange specialists disseminate information to market participants by displaying price schedules consisting of bid prices, ask prices, bid depths, and ask depths. We examine how specialists update these price schedules in a simultaneous equations model. We find that changes in the best prices and depths on the limit order book have a significant impact on the posted price schedule, while the effects of transactions and order activity are secondary. Furthermore, we show that specialists revise prices and depths differently, but find no evidence that they revise the price schedule in response to changes in inventory.